Data challenges and opportunities for environmental management of North Sea oil and gas decommissioning in an era of blue growth. (November 2018) - Murray, Fiona; Needham, Katherine; Gormley, Kate; Rouse, Sally; Coolen, Joop W.P.; Billett, David; Dannheim, Jennifer; Birchenough, Silvana N.R.; Hyder, Kieran; Heard, Richard; Ferris, Joseph S.; Holstein, Jan M.; et al.
Abstract: Maritime industries routinely collect critical environmental data needed for sustainable management of marine ecosystems, supporting both the blue economy and future growth. Collating this information would provide a valuable resource for all stakeholders. For the North Sea, the oil and gas industry has been a dominant presence for over 50 years that has contributed to a wealth of knowledge about the environment. As the industry begins to decommission its offshore structures, this information will be critical for avoiding duplication of effort in data collection and ensuring best environmental management of offshore activities. This paper summarises the outcomes of a Blue Growth Data Challenge Workshop held in 2017 with participants from: the oil and gas industry; the key UK regulatory and management bodies for oil and gas decommissioning; open access data facilitators; and academic and research institutes. Here, environmental data collection and archiving by oil and gas operators in the North Sea are described, alongside how this compares to other offshore industries; what the barriers and opportunities surrounding environmental data sharing are; and how wider data sharing from offshore industries could be achieved. Five primary barriers to data sharing were identified: 1) Incentives, 2) Risk Perception, 3) Working Cultures, 4) Financial Models, and 5) Data Ownership. Active and transparent communication and collaboration between stakeholders including industry, regulatory bodies, data portals and academic institutions will be key to unlocking the data that will be critical to informing responsible decommissioning decisions for offshore oil and gas structures in the North Sea. Highlights: The oil and gas industry has a 50 year archive of environmental data. There have been successful collaborations to make these data widely available. A standardised approach is now needed to facilitate environmental data sharing.